Numerical Methods and Computer Simulations in Energy Analysis - Kamiński, Marcin; Juan, Angel A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Numerical analysis and computer simulations are becoming increasingly important in modeling of new sources and methods of harvesting, transforming and storing energy from its renewable sources. A similar trend is also observed in relation to environmental impacts on people and the buildings in which they use to live or stay, as well as the impact of everyday devices, machines and industrial installations on the quality of air and drinking water. This collection provides an overview of contemporary methods, algorithms and results in this broad and important field of human knowledge. Particularly noteworthy here are works in the area of machine learning and artificial intelligence, where the progress of computer methods and the interest of researchers from many fields seem to be the greatest. The use of statistical and stochastic algorithms that make it possible to take into account the impact of wind, humidity, moisture, temperature and sunlight on the immediate human environment remains still a great challenge.